Extrusion–calendering process of single‐polymer composites based on polyethylene. Issue 12 (28th February 2018) - Wang, Jian; Du, Ziran; Lian, Tong
Abstract : The extrusion–calendering process was realized successfully to produce the potential and easily recyclable single‐polymer composites (SPCs). This approach makes it possible to produce SPCs continuously and avoids the drawbacks involving a long cycle time, inconvenient operation, and expensive cost. Low‐density polyethylene (LDPE) reinforced with ultrahigh molecular weight polyethylene (UHMWPE) fabric was prepared. Based on orthogonal and single factor experiments, the effects of die temperature, screw speed, and rolls speed were investigated. The tensile and interfacial properties of the LDPE/UHMWPE SPCs were evaluated through tensile and T‐peel tests. The best tensile strength of 78.8 ± 7 MPa was obtained in the LDPE/UHWMPE SPCs with a fiber volume fraction of 11.2% and a void content of 0.01%. The peel strength was significantly improved, 22.4 N/10 mm was achieved. The morphology observed using scanning electron microscopy (SEM) further determined the fiber–matrix interfacial adhesion and the effects of processing parameters. POLYM. ENG. SCI., 58:2156–2165, 2018. © 2018 Society of Plastics Engineers